The Impact of Two Doses of Vitamin K2 (Menaquinone-7) on Doxorubicin-Induced Hepatotoxicity in Rats - Ruaa Fadhil Abbas AlZubaidi; Nada Naji Al-Shawi (College of Pharmacy University of Baghdad, 2017)
The objective of this study was to evaluate the impact two doses of Menaquinones-7 on hepatotoxicity induced by doxorubicin in rats. Sixty adult rats of both sexes were used in this study; the animals were randomly enrolled into six groups of 10 animals each. Group I: negative control (rats administered distilled water); Group II: Menaquinones-7 at a dose of  16 Âµg/kg; Group III: Menaquinones-7 at a dose of 48 Âµg/kg; Group IV: positive control (Doxorubicin 15 mg/kg); Group V: Menaquinones-7 at a dose of 16 Âµg/kg administered prior to a single dose of Doxorubicin 15 mg/kg; Group VI: Menaquinones-7 at a dose of 48 Âµg/kg administered prior to a single dose of  Doxorubicin 15 mg/kg. On day twelve of the study, blood was collected for serum preparation for the estimation of alanine aminotransferase (ALT), alkaline phosphatase (ALP), and total bilirubin (TB). The liver of each animal was excised for histological examination. High dose of MK-7 significantly (P<0.05) decreased serum ALT, ALP, and TB and there was an improvement in the histopathological lesions of the liver in group V and group VI compared to group IV. In conclusion, MK-7 may have protective effect against Dox-induced hepatotoxicity in rats.